If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 3n = 12 Solving m + 3n = 12 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3n' to each side of the equation. m + 3n + -3n = 12 + -3n Combine like terms: 3n + -3n = 0 m + 0 = 12 + -3n m = 12 + -3n Simplifying m = 12 + -3n
| 6x^2-23x+7= | | 2j=222 | | 4.87=n+0.87 | | x=-16t^2+400 | | 6p-27-53=4 | | 5.4=t+(-6.1) | | 2(n+1.5)=4.5 | | 117.345+m=200 | | 4v^2-14v-15= | | 9x-5=2x+16 | | -58.109=v-47.736 | | 2x^2+.25x=0 | | -27-53+4=6x | | -0.08=f+0.07 | | -7(t+3)=0 | | a(2a^2+3)+(a^2-10)= | | -x=0.12 | | 6.21=e+(-3.48) | | 4x+8=2x-1 | | 4x-10=95 | | -13.8=h+15.603 | | -176=7x+4(-7x-2) | | 47+5k=9(k+3) | | 2(9-8)= | | -165=-3x+6(-x-11) | | -22=p+13.7 | | 3(x-2)+46=-2x | | k-263.48=-381.09 | | 9c-3c=-8 | | x-19.7=17.48 | | 2x+4(2x-5)=-110 | | 8-9(4-1)(3-4)= |